Self‐Standing Membrane of Hetero‐Assembled Nanosheets with Drastically Enhanced Emission and Tunable Color. Issue 21 (4th August 2022) - Bai, Mingjun; Li, Junyi; Liu, Xiaohe; Sasaki, Takayoshi; Ma, Renzhi
Abstract: Self‐standing membranes are fabricated by filtrating corresponding superlattice units of luminescent rare‐earth hydroxide (e.g., europium doped gadolinium hydroxide (GdEu), terbium doped gadolinium hydroxide (GdTb)) nanosheets, and semiconducting oxide (e.g., Ti0.87 O2 0.52− (TiO), TaO3 − (TaO)) nanosheets. The superlattice membrane of GdEu/TiO and GdTb/TaO shows drastically enhanced emission intensity 21.5 and 38.6 times higher than that of GdEu and GdTb, respectively, as well as a higher color purity and longer lifetime. By further integrating both GdEu/TiO and GdTb/TaO superlattices, the (GdEu/TiO)/(GdTb/TaO) integrated membrane exhibits tunable color under different excitations. The superior performance is ascribed to the enhanced energy absorption by the semiconducting oxide nanosheets and efficient energy transfer to rare‐earth hydroxide nanosheets across the nanointerface. Moreover, the superlattice membrane displays strong and stable cathodoluminescence under continuous cathode‐ray radiation. This work demonstrates a new strategy for large‐scale fabrication of self‐standing membranes, which are promising for practical applications in multicolor display fields. Abstract : Self‐standing membranes are fabricated by filtrating corresponding suspensions of nanosheets and superlattice units. The superlattice membranes containing hetero‐assembled rare‐earth hydroxide and oxide nanosheets show drastically enhanced emission intensity, higher color purity, and longer lifetime. Furthermore, an integrated superlattice membrane exhibits excitation wavelength‐dependent tunable colors, promising a high potential for multicolor display applications.